Emotional intelligence and online learning readiness among students in a technical university in Malaysia - Kasim, Helmi Mohd; Md Saad, Mohd Shamsuri; Ibrahim, Ismail; Rajikon, Muhd Akmal Noor (Research and Scientific Innovation Society, 2025)
The main aim of this study is to investigate the influence of emotional intelligence on students’ online learning readiness in a public university in Malaysia. Four hundred and ninety-six students from eight faculties at the Universiti Teknikal Malaysia Melaka (UTeM) participated in this study which was conducted fully online using Google Forms due to the pandemic issue. The students completed the Online Learning Readiness (OLR) Scale and the Trait Emotional Intelligence Scale – Short Form (TEIS-SF) to assess their online learning readiness and emotional intelligence. According to the descriptive results, all dimensions related to students' online learning readiness scored above medium mean scores, and almost all dimensions of emotional intelligence, with the exception of the social dimension, scored above-medium mean scores. Correlation analysis reveals a significant positive relationship between students' emotional intelligence and their readiness for online learning. The key findings in this study could be used to facilitate online learning by educators and students.